Dying justice : a case for decriminalizing euthanasia and assisted suicide in Canada - Downie, Jocelyn Grant, 1962- (University of Toronto Press, 2004)
"The legal status of assisted death in Canada is in urgent need of clarification and reform. However, this process must be informed by a careful, thorough, and thoughtful analysis of the issues. In Dying Justice, Jocelyn Downie provides an up-to-date and comprehensive review of significant developments in the current legal status of assisted death in Canada. She then recasts the framework for analysis in terms of the nature of the decision for assisted death. Refusals of treatment and requests for assisted suicide and euthanasia, the author argues, should be respected if they are made voluntarily by informed and mentally competent individuals." "Downie proposes a system for Canada that is both less restrictive than the status quo with respect to assisted suicide and euthanasia and more restrictive with respect to the withholding and withdrawal of potentially life-sustaining treatment. On the basis of a thorough review of all of the major arguments made against permitting assisted suicide and euthanasia, Downie calls for a legislative regime that permits some assisted suicide and euthanasia, but also sets out strict criteria that must be met before refusals of treatment would be respected."--Jacket.